Implementasi Program Linear pada Efisiensi Penugasan Jam Kerja Divisi Pengadaan PT. Pelindo Multi Terminal Dengan Metode Hungarian - Rahma Aulia; Sabrina Nasution; Rina Filia Sari; Muliawaty, Muliawaty (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This research was conducted with the aim of optimizing the assignment of working hours in the Procurement Division of PT. Pelindo Multi Terminal through the application of the Hungarian method. The fundamental problem faced is the imbalance between the number of permanent workers and the high workload that must be completed, thus creating a risk of inefficiency in the operational process. To address this problem, a quantitative approach was used with linear programming modeling techniques designed to produce a more systematic and measurable assignment allocation. Through the analysis conducted, an optimal solution was obtained regarding the distribution of working hours, where the total working time can be reduced to 10,120 minutes per month, lower than the previously set maximum limit of 10,560 minutes per month. These results indicate that the application of the Hungarian method is not only able to reduce excessive workloads on some employees, but also ensures a more proportional distribution of assignments among all available workers. In addition, this method can increase operational effectiveness because each worker receives a load according to their capacity, so that the risk of fatigue or decreased performance can be minimized. The findings of this study confirm that the Hungarian method is an alternative work scheduling strategy that is efficient to be applied in industrial environments with high task complexity. Proper implementation can also support the achievement of overall company productivity, improve the quality of human resource management, and strengthen the company's competitiveness in facing future operational challenges.